The secret language of color : science, nature, history, culture, beauty of red, orange, yellow, green, blue & violet - Eckstut, Joann; Eckstut, Arielle (New York, NY : Black Dog & Leventhal Publishers, 2013)
Explores color's countless manifestations, providing insight into such phenomena as the visible spectrum, light absorption and reflection, how humans see color, how vision evolved, the sky, rainbows, colored gems, animal pigmentation, how animals use color to find mates and to protect themselves, and the use of color in human religion, ritual, design, navigation, communication, and personal identity.
Pub Weekly, August 2013
Includes bibliographical references (p. 234-235) and index.
Adult
Keywords: Color; Color